A construção discursiva da legitimidade do profissional de RH: o caso do processo de seleção docente de uma IES - Hofmeister, Deise Léia Farias (2013)
The work includes the proposal that seeks to investigate the legitimacy of Human Resources as well as the legitimacy of the actions of the Human Resources professional. The effort undertaken here is focused on exploring how the changing discursive content showed changes that aimed to establish new practices in the process selection of teachers. Whereas the discursive content leads to reinterpretation seeking to emphasize the achievement of an ideology, which is linhed to a dominant production and associated with the influence of instrumental rationality of Management, contstructs a Human Resources that develop and combine the demands of organizational practices and emergency measure following the company's interests in achieving goals that characterize economic and market competitiveness. These consequences make it possible to confirm the existence of communicative distortion declared by different actors involved in the transformation of the practice of selecting teachers for IES. The research methodology was qualitative in nature, based on a case study in which we interviewed three groups of professionals of IES the administration, coordination of the course and a Human Resources professional, adopting the technique of Discourse Analysis. The results of the research show that the speech which involves the legitimacy of Human Resources as well as the legitimacy of the professional considers only the aspects that based on the creation of mechanisms that provide the feedback for the actions of HR.